ANALISIS PERHITUNGAN PERSEBARAN DOSIS RADIASI PESAWAT SINAR-X DALAM BENTUK KURVA ISODOSIS YANG DIWUJUDKAN DENGAN PROGRAM KOMPUTER BERBASIS DELPHI - , ANGGRATA A, Ir. Mondjo, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the radiation installation such as radiologic installation, the safety of radiation workers must be a concern. Every worker has to identify their workplace radiation by specific information about radiation level, especially a secondary radiation. The specific information about radiation can be visualized in Isodoses Curve. The distribution and amount of X-Ray secondary radiation can be analyzed. Making a computer program as a visual aid, can help to analyze isodose curve easier. In this research, a secondary dose rate radiation as a primary data has been measured using water phantom as a scattering material at 90 degrees of scattering angle and the X-Ray tube directed downwards to patient table perpendicularly in 7 directed points around water phantom. In each direction, a range of data collection points have been varied in 3 levels. Then, a collected data will be processed by calculating the distribution of dose rate at each direction, and then connects the same dose rate inter-direction, and finally calculates the dose rate in current position. Based on these steps, a computer program will be created based on Delphi language. Testing an isodose curve program is performing by using a comparison data analysis of dose rate calculation using program and the measurements. The results of the test indicates that the difference of the dose rate values between the program calculation and measurement ranging from 10.830-32.050 % and mean difference approximately 17.334%. The results of the test from 5 times showed that 3 results of the testing program calculations are in the interval of measurement results, while 2 remaining results are outside of the interval measurement results.